"FAKE!" : zomerproject beeldende kunst stad Aalst 2010. - de Nys, Jan; Stedelijk Museum, Aalst; publieke ruimte, Aalst (Aalst : [s.n.], 2010)
Aerts, Michael ; Angenot, Eric ; Berlanger, Marcel ; Bourgeat, Lilean ; Bourgeois, Jean Daniel ; Bragigand, Franck ; Buffe, Nicolas ; Bulfin, Alan ; Coolen, Caroline ; Cotteleer, Anton ; et al.
"FAKE!", Stedelijk Museum, Aalst
kunstcatalogus
Keywords: Aalst